Identification of Presymptomatic and Asymptomatic Cases Using Cohort-Based Testing Approaches at a Large Correctional Facility—Chicago, Illinois, USA, May 2020. (3rd December 2020) - Wadhwa, Ashutosh; Fisher, Kiva A; Silver, Rachel; Koh, Mitsuki; Arons, Melissa M; Miller, David A; McIntyre, Anne F; Vuong, Jeni T; Kim, Kaylee; Takamiya, Mayuko; Binder, Alison M; Tate, Jacqueline E; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) continues to cause significant morbidity and mortality worldwide. Correctional and detention facilities are at high risk of experiencing outbreaks. We aimed to evaluate cohort-based testing among detained persons exposed to laboratory-confirmed cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in order to identify presymptomatic and asymptomatic cases. Methods: During 1–19 May 2020, 2 testing strategies were implemented in 12 tiers or housing units of the Cook County Jail, Chicago, Illinois. Detained persons were approached to participate in serial testing (n = 137) and offered tests at 3 time points over 14 days (day 1, days 3–5, and days 13–14). The second group was offered a single test and interview at the end of a 14-day quarantine period (day 14 group) (n = 87). Results: 224 detained persons were approached for participation and, of these, 194 (87%) participated in ≥1 interview and 172 (77%) had ≥1 test. Of the 172 tested, 19 were positive for SARS-CoV-2. In the serial testing group, 17 (89%) new cases were detected, 16 (84%) on day 1, 1 (5%) on days 3–5, and none on days 13–14; in the day 14 group, 2 (11%) cases were identified. More than half (12/19; 63%) of the newly identified cases were presymptomatic or asymptomatic. Conclusions: Our findings highlight the utility of cohort-based testing promptly after initiating quarantine within a housing tier. Cohort-based testing efforts identified new SARS-CoV-2 asymptomatic and presymptomatic infections that may have been missed by symptom screening alone. Abstract : Our findings suggest that early cohort-based testing in detained persons helped identify new SARS-CoV-2 asymptomatic and presymptomatic infections that may have been missed by symptom screening alone. Frequency of testing may be dependent on status of outbreak in the facility.